The concept of a contract for creative work. Critical analysis - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The author of the study makes critical evaluation of the concept of a contract for specific creative (artistic) work that has been in force for some time in judicial decisions. Its essence consists in limiting the scope of application of specific work contracts in legal transactions only to those cases where the work which results from the contract meets the features of the piece of work in the meaning of the provisions of copyright law. Under this concept, the acceptability of using the contract for specific work is permitted only in situations where the result is original creation, which is unique, protected by copyright and requiring special skills from the author being commissioned to do the work, constituting an expression of their creativity and specific skills. The author of the study, showing the significant shortcomings of the analyzed concept, tries to prove that de lege lata it has no grounds in the applicable law, and the interpretation of the provisions of the Civil Code governing the contract for specific work made by judicature is an interpretation of contra legem. De lege ferenda should consider subjecting a contract for specific work to social security and health insurance and creation of a separate definition of a contract for specific work, which will apply only to the law of social insurance.